Desing Thinking como metodología para la enseñanza y aprendizaje del cuidado de los servicios ecosistémicos en los habitantes de la parroquia Sicalpa del Cantón Colta. - Ortiz Toala, Josue Alejandro (2024)
The present research named “Desing Thinking as a Methodology for Teaching and Learning the Care of Ecosystem Services in the Inhabitants of the Sicalpa parish of the Colta canton”, was developed with the aim of proposing an innovative methodology for the development of a physical manual - digital that allows the learning and teaching of the care of ecosystem services through the study of aquatic macroinvertebrates in the Sicalpa parish of the Colta canton, promoting the study of new methodologies to integrate them into modern learning. Although at present there has been evolution in various aspects such as technology, the study itself, health and other activities, the educational context in places surrounding the city remains with poorly updated learning where traditionalism It is the main methodology for teaching new knowledge to students, preventing the renewal of teachings and educational strengthening; As a result of these failures, the same system causes society to not be able to visualize the reality of the territory where they live, taking into account the environmental situation, such as air and water pollution or the deterioration of the soil where they use it for their purposes. work activities. The importance of new tools for learning techniques that facilitate the teaching and understanding of environmental care is of interest to the academy, with the purpose of integrating Desing Thinking into an innovative Methodology, because our society currently seeks a structured education. and, above all that the main axis is not only learning and evaluation.